68 HOW PREVALENT IS UNSUSPECTED MITRAL AND AORTIC REGURGITATION?. (1st March 2006) - Stefano, G. T.; Fox, K.; Schluchter, M.; Hoit, B. D.
Abstract : Introduction: Doppler echocardiography plays a critical role in identifying valvular insufficiency that may complicate the use of phen-fen and related drugs. However, the prevalence of unsuspected, preexisting valvular regurgitation in a large, heterogeneous population is poorly defined. Methods: 6, 861 records were examined from consecutive individuals without known or suspected valve disease referred to the UHC echo laboratory for nonvalvular-related indications from 2001-2003. Mitral (MR) and aortic (AI) regurgitant severity was graded using a clinical composite of published 2-D, spectral, and color flow-Doppler methods. Multiple logistic analysis ( SPSS, v13) was used to model clinical variables (age, gender, left ventricular ejection fraction [LVEF], body mass index [BMI], history of hypertension [HTN], LV hypertrophy [LVH], history of coronary disease [CAD]) and valvular morphology. Results: Prevalence estimates for moderate or greater MR and mild or greater AI as a function of age are shown in the figure. Female gender predicted MR (OR 2.12, 95% CI 1.78-2.53), but AI was gender neutral. Regurgitant severity increased with decreasing EF and BMI, and the presence of LVH, HTN, and CAD were not predictive. Regurgitation prevalence was significantly influenced by both nonspecific and specific valve abnormalities. Conclusions: The prevalence of moderate or greater MR and mild or greater AI is substantial, increases exponentially with age, and is predicted by commonly used clinical variables. These prevalence estimates should be considered when assessing the finding of unanticipated MR or AI on echocardiogram.